Hydrodynamic analysis of floating offshore solar farms subjected to regular waves - Al-Yacouby, A.M. (Springer Science and Business Media Deutschland GmbH, 2020)
In the Malaysian water, most of offshore platforms rely on fossil fuels to produce electricity for their power generation. However, due to concerns related to depletion of fossil fuels and the greenhouse gas (GHG) emissions, the Malaysian government is moving towards the application of renewable energy resources. Floating solar farms are comparatively new in the Malaysian water, and in-depth investigation is needed to better understand the performance of these types of floaters when placed in the open sea. This paper is intended to conduct a parametric study on the dynamic responses of a floating solar farm for Malaysian offshore applications. In this study, the dynamic responses of the floating solar farm are determined using analytical methods, and then the results are validated using Computational Fluid Dynamics (CFD). The important parameters covered in this study are the wave heights, wave periods, water depths, and the diameter of pontoons. The results show that wave heights, wave periods, and pontoon diameters have major influence on the hydrodynamic forces, while the water depth has comparatively minor influence on the dynamic responses of the floating offshore solar farm. Â© Springer Nature Singapore Pte Ltd 2020.